Kaira, la revolución digital en la industria textil. Una propuesta empresarial - Jorge Raúl Ramírez-Zambrano; María Valentina García; Misael Andrés Cadena-Albarracín; David Alonso Castro-Ordoñez (Mundo Fesc)
Based on studies conducted on smart clothing, ICT adoption in different scenarios, and the application of QR code technology in different fields; this paper proposes the creation of KAIRA [1] under an innovative value proposition that incorporates the use of technology and a differentiating value proposition for the industrial, professional and business services sector of the city of Cúcuta for the period 2019-2020. To this end, the research was developed under an exploratory, descriptive, and mixed approach, as it contrasts theory with reality and identifies causes and effects to describe the relationship between literature and facts; In addition, it uses qualitative and quantitative tools to support the research. The results show a considerable potential market share that is financially viable despite some signs that reflect the need for improvement actions, and finally, a consolidated business model is obtained from a general economic, social, and environmental perspective; from an operational, legal, and strategic perspective. Finally, it is concluded that the project is feasible and relevant because it generates positive impacts at the regional level, both competitively and culturally.